Case report: From metabolic instability to remission: a case of pheochromocytoma presenting as atypical diabetes - Cao, Chuqing; Xue, Pingyan; Yang, Xuefeng; Huang, Fansu; Xie, Yuting; Zhou, Zhiguang (Frontiers in Endocrinology, 2026)
IntroductionPheochromocytoma is a well-established cause of secondary hypertension and can lead to dysglycemia. However, its initial presentation as atypical diabetes, characterized by severe glycemic instability, is uncommon and poses a significant diagnostic challenge.Case presentationA 49-year-old non-obese Chinese woman presented with a 15-month history of progressive polyuria and polydipsia. Initially diagnosed with type 2 diabetes, she developed significant glycemic variability with recurrent hypoglycemia and profound hyperglycemia, alongside a rapid decline in β-cell function. During hospitalization, paroxysmal hypertension was observed. Biochemical testing confirmed markedly elevated catecholamines and metabolites. Imaging identified a left adrenal mass, confirmed as pheochromocytoma following laparoscopic adrenalectomy. Postoperatively, all antidiabetic medications were discontinued. At 3-month follow-up, she achieved sustained normoglycemia with restored β-cell function and normalized blood pressure.ConclusionsThis case demonstrates that pheochromocytoma can induce a severe, reversible form of diabetes characterized by profound metabolic instability and marked glycemic variability. It highlights the necessity of including pheochromocytoma in the differential diagnosis of patients with atypical, labile diabetes, especially when paroxysmal symptoms are present. Early surgical intervention can reverse these metabolic derangements, often leading to diabetes remission.